Polymer composition for non-aqueous secondary batteries, cathode for non-aqueous secondary batteries, non-aqueous secondary battery and use of polymer composition for non-aqueous secondary batteries
A polymer composition with controlled electrolyte swelling and emulsifier content addresses handling and cycle performance issues in non-aqueous secondary batteries, ensuring stable electrode performance and capacity retention.
Patent Information
- Application Number
- JP2023116133
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-24
AI Technical Summary
Existing polymer compositions for non-aqueous secondary batteries, particularly lithium ion secondary batteries, face challenges in handling ease and cycle characteristics, including poor defoaming properties which lead to local irregularities on the electrode surface, impairing cycle performance.
A polymer composition comprising specific ethylenic monomers with controlled electrolyte swelling degrees and emulsifier content, along with a glass transition temperature of 20°C or less, enhances defoaming properties and cycle characteristics by moderating electrolyte swelling and improving adhesion.
The composition achieves excellent defoaming properties and cycle characteristics, maintaining capacity and stability over repeated cycles, even in positive electrodes with conductive additives.
Smart Images

Figure 2025012930000001 
Figure 2025012930000002 
Figure 2025012930000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer composition for a non-aqueous secondary battery, a positive electrode for a non-aqueous secondary battery, a non-aqueous secondary battery, and use of the polymer composition for a non-aqueous secondary battery. [Background technology]
[0002] In recent years, research on non-aqueous secondary batteries, especially lithium-ion secondary batteries, has been actively conducted as an energy technology to reduce the burden on the environment. Lithium-ion secondary batteries have a large capacity per unit weight or volume compared to other battery systems, and are suitable for large-capacity and miniaturization. For example, in the automotive field, exhaust gas regulations in each country are becoming stricter every year, and with the shift to electric vehicles such as EVs, the demand for lithium-ion secondary batteries is increasing. One method for producing an electrode for a lithium ion secondary battery or the like is to apply a liquid composition (slurry) in which a binder, a thickener, etc. is added to an electrode active material onto a current collector surface and then dry the composition to form an electrode layer on the current collector. Here, styrene-butadiene polymer particle latex is known as a binder that has high adhesive strength with the metal current collector and is used in aqueous blends. Binders have the function of improving the adhesion between solid active materials, between an active material and a current collector, or between an active material and a separator.
[0003] Patent Document 1 proposes a polymer composition for secondary batteries in which a compound whose electrolyte swelling degree falls within a specific numerical range is added and mixed in a specific ratio to a specific polymer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2022-131253 Summary of the Invention [Problem to be solved by the invention]
[0005] It is said that the polymer composition described in Patent Document 1 can achieve both high levels of cycle characteristics. However, the inventors have found through their studies that there is still room for improvement in the handleability of the composition (e.g., defoaming property) and the cycle characteristics of a secondary battery obtained by applying the composition.
[0006] The problem to be solved by the present invention is to provide a polymer composition for a non-aqueous secondary battery, which is excellent in defoaming properties and cycle characteristics, a positive electrode for a non-aqueous secondary battery, a non-aqueous secondary battery, and use of the polymer composition for a non-aqueous secondary battery. [Means for solving the problem]
[0007] The present invention includes the following aspects. <1> a content of the units U1 exceeding 50% by mass and a content of the units U2 being 5% by mass or more and less than 50% by mass or less of all units derived from ethylenically unsaturated monomers constituting the polymer particles, the polymer composition having a swelling degree in an electrolyte solution of 1.30 times or less, and an emulsifier of 0.01% by mass or more and 1.0% by mass or less, based on 100% by mass of all units derived from ethylenically unsaturated monomers constituting the polymer particles; <2> The emulsifier is a sulfonic acid or a salt thereof. <1> The polymer composition for non-aqueous secondary batteries according to claim 1. <3> The degree of neutralization is 5 mol % or more and less than 40 mol %. <1> or <2> The polymer composition for non-aqueous secondary batteries according to claim 1. <4> The solid content of the water-soluble component is 1.0% by mass or less. <1> ~ <3> 10. The polymer composition for a non-aqueous secondary battery according to claim 9, <5> The content of the unit U1 is more than 50% by mass, and the content of the unit U2 is 5% by mass or more and less than 25% by mass, based on 100% by mass of all units derived from ethylenically unsaturated monomers constituting the polymer particles. <1> ~ <4> 10. The polymer composition for a non-aqueous secondary battery according to claim 9, <6> The ethylenic monomer M1 includes 2-ethylhexyl acrylate. <1> ~ <5> 10. The polymer composition for a non-aqueous secondary battery according to claim 9, <7> The ethylenic monomer M2 includes an ethylenically unsaturated carboxylic acid or an alkali metal salt thereof. <1> ~ <6> 10. The polymer composition for a non-aqueous secondary battery according to claim 9, <8> The ethylenic monomer M2 contains (meth)acrylic acid or an alkali metal salt thereof. <1> ~ <7> 10. The polymer composition for a non-aqueous secondary battery according to claim 9, <9> The polymer particles have a glass transition temperature of 20° C. or lower as measured by a differential scanning calorimeter (DSC). <1> ~ <8> 10. The polymer composition for a non-aqueous secondary battery according to claim 9, <10> The average particle size of the polymer particles is 50 nm or more and 800 nm or less. <1> ~ <9> 10. The polymer composition for a non-aqueous secondary battery according to claim 9, <11> The polymer particles further include an isothiazolinone compound, and the content of the isothiazolinone compound is 0.0001% by mass or more and 1.0% by mass or less with respect to 100% by mass of the polymer particles. <1> ~ <10> 10. The polymer composition for a non-aqueous secondary battery according to claim 9, <12> <1> ~ <11> 2. A positive electrode for a non-aqueous secondary battery, comprising the polymer composition for a non-aqueous secondary battery according to claim 1. <13> <1> ~ <11> 2. A non-aqueous secondary battery comprising the polymer composition for non-aqueous secondary batteries according to claim 1. <14> <1> ~ <11> 2. Use of the polymer composition for a non-aqueous secondary battery according to claim 1 as a material for a positive electrode of a non-aqueous secondary battery. Effect of the Invention
[0008] According to the present invention, it is possible to provide a polymer composition for a nonaqueous secondary battery, which is excellent in defoaming properties and cycle characteristics, a positive electrode for a nonaqueous secondary battery, a nonaqueous secondary battery, and use of the polymer composition for a nonaqueous secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention (hereinafter simply referred to as "the present embodiment") will be described in detail. The following embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out with appropriate modifications within the scope of the gist of the present invention. In this specification, when a numerical value or physical property value is enclosed before and after "~", the values before and after the "~" are included. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples. In the description of groups (atomic groups) in this specification, when there is no indication of substituted or unsubstituted, the term encompasses both unsubstituted and substituted groups. For example, the term "alkyl group" encompasses not only alkyl groups without a substituent (unsubstituted alkyl groups) but also alkyl groups with a substituent (substituted alkyl groups). In this specification, "(meth)acrylic" includes both methacryl and acrylic. In this specification, the content of each component means the total content of the corresponding component, unless otherwise specified.
[0010] ≪Polymer composition for non-aqueous secondary batteries≫ The polymer composition for non-aqueous secondary batteries of the present embodiment (also simply referred to as the composition in the present embodiment) includes polymer particles having a unit U1 (also simply referred to as U1) derived from an ethylenic monomer M1 (also simply referred to as M1) and a unit U2 (also simply referred to as U2) derived from an ethylenic monomer M2 (also simply referred to as M2), the ethylenic monomer M1 has an electrolyte swelling degree of 1.40 times or less, the ethylenic monomer M2 has an electrolyte swelling degree of 1.20 times or less, the content of the unit U1 is more than 50 mass% and the content of the unit U2 is 5 mass% or more and less than 50 mass%, the electrolyte swelling degree of the polymer particles is 1.30 times or less, and the emulsifier is 0.01 mass% or more and 1.0 mass% or less, based on 100 mass% of all units derived from the ethylenic unsaturated monomers constituting the polymer particles.
[0011] In this technical field, from the viewpoint of improving the electrolyte resistance, a monomer having an SP value far from the SP value of the electrolyte may be selected. In this case, it is required to select a monomer lacking the balance between hydrophobicity and hydrophilicity, and the copolymerization of the monomer tends to be insufficient. To solve this problem, it is possible to add an emulsifier, but a binder containing an emulsifier tends to have poor defoaming properties when preparing a slurry. When the defoaming properties are poor, partial unevenness occurs on the electrode surface, and electrodes with large unevenness tend to impair cycle characteristics. As a result of extensive investigations, the present inventors have found that the composition of the present embodiment including the above-mentioned features can achieve excellent defoaming properties and cycle characteristics.
[0012] <Polymer particles> The polymer particles of this embodiment have units U1 derived from an ethylenic monomer M1 and units U2 derived from an ethylenic monomer M2.
[0013] [Electrolyte swelling degree of ethylenic monomer M1] The electrolyte swelling degree of M1 is 1.40 times or less. By controlling the swelling degree in the electrolyte to 1.40 times or less, the swelling ratio of the polymer particles can be appropriately controlled, and excellent cycle characteristics can be obtained. From the above viewpoint, the degree of swelling in the electrolyte of M1 is preferably 1.35 times or less, and more preferably 1.30 times or less. The electrolyte swelling degree of M1 may be 1.25 times or more, and may be more than 1.20 times.
[0014] The degree of swelling of a monomer in an electrolyte means the degree of swelling of a polymer polymerized only from a monomer when immersed in an electrolyte.
[0015] [Method for measuring the degree of swelling of a monomer in an electrolyte] The degree of swelling of the monomer in the electrolyte is measured by the following method. The composition containing the polymer polymerized only from the monomer is left to stand in an oven at 130°C for 1 hour to dry. A film of the polymer obtained by drying is cut out, and the mass of the film (Wa:g) is measured. The cut sample is placed in a 50mL vial together with 20g of a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 2 (volume ratio), and the mixed solvent is allowed to penetrate at 60°C for 1 day. Thereafter, the film is taken out, the electrolyte is wiped off, and the mass of the film (Wb:g) is measured. The film is washed with the mixed solvent, the mass (Wb:g) is measured, and the swelling degree of the polymer in the electrolyte is calculated using the following formula. Electrolyte swelling rate (%) = (Wb / Wa) x 100
[0016] [Electrolyte swelling degree of ethylenic monomer M2] The electrolyte swelling degree of M2 is 1.20 times or less. By controlling the swelling degree in the electrolyte to 1.20 times or less, the swelling rate of the polymer particles can be appropriately controlled, and excellent cycle characteristics can be obtained. From the above viewpoint, the degree of swelling in the electrolyte of M2 is preferably 1.15 times or less, and more preferably 1.10 times or less. The degree of swelling in the electrolyte of M2 may be 1.05 times or more, or may be 1.00 times or more.
[0017] The degree of swelling in an electrolyte solution can be adjusted to fall within the above range, for example, by appropriately selecting a monomer M1 having a low or high SP value.
[0018] The content of the unit U1 is more than 50% by mass relative to 100% by mass of all units derived from the ethylenically unsaturated monomers constituting the polymer particles. When the content of U1 is more than 50% by mass, the balance between defoaming properties and cycle characteristics is excellent. From the above viewpoints, the content of U1 is preferably 55% by mass or more, more preferably 60% by mass or more, and further preferably 65% by mass or more. From the viewpoint of achieving an excellent balance between defoaming properties and cycle characteristics, the content of U1 is preferably 99% by mass or less, more preferably 95% by mass or less, and even more preferably 92% by mass or less.
[0019] The content of the unit U2 is 5% by mass or more and less than 50% by mass relative to 100% by mass of all units derived from the ethylenically unsaturated monomers constituting the polymer particles. By having the content of U2 be 5% by mass or more and less than 50% by mass, an excellent balance between defoaming properties and cycle characteristics is achieved. From the above viewpoints, the content of U2 is preferably 7% by mass or more, and more preferably 10% by mass or more. From the viewpoint of achieving an excellent balance between defoaming properties and cycle characteristics, the content of U2 is preferably 45 mass % or less, more preferably 35 mass % or less, and further preferably 24 mass % or less.
[0020] In the composition of this embodiment, it is preferred that the content of units U1 is more than 50 mass% and the content of units U2 is 5 mass% or more and less than 25 mass%, relative to 100 mass% of all units derived from the ethylenically unsaturated monomers constituting the polymer particles.
[0021] M1 and M2 may have the same electrolyte swelling degree. In this case, an ethylenic monomer having a content of the resulting unit of more than 50 mass% relative to 100 mass% of all units derived from the ethylenic unsaturated monomers constituting the polymer particles is M1, and an ethylenic monomer having a content of the resulting unit of less than 50 mass% relative to 100 mass% of all units derived from the ethylenic unsaturated monomers constituting the polymer particles is M2. The degree of swelling of M1 in the electrolyte solution is preferably greater than the degree of swelling of M2 in the electrolyte solution.
[0022] M1 and M2 can be used without any particular limitation. For example, M1 and M2 can be 2-ethylhexyl acrylate, (meth)acrylic acid, acrylamide, etc. The monomers used as M1 or M2 can be appropriately selected from the above.
[0023] As M1, acrylic acid esters such as 2-ethylhexyl acrylate, heptyl acrylate, octyl acrylate, isodecyl acrylate, and the like, and methacrylic acid esters such as octyl methacrylate, lauryl methacrylate, octadecyl methacrylate, tetradecyl methacrylate, and the like are preferable, and 2-ethylhexyl acrylate is more preferable.
[0024] M2 is preferably an ethylenically unsaturated carboxylic acid such as (meth)acrylic acid or an alkali metal salt thereof, or acrylamide, and more preferably includes at least one selected from the group consisting of (meth)acrylic acid and acrylamide.
[0025] M2 preferably contains an ethylenically unsaturated carboxylic acid or an alkali metal salt thereof. It is also preferable that M2 contains (meth)acrylic acid or an alkali metal salt thereof.
[0026] The polymer particles in this embodiment may contain units derived from monomers other than M1 and M2. Examples of other monomers include (meth)acrylic acid esters not corresponding to the ethylenic monomer M1, such as methyl (meth)acrylate, ethyl (meth)acrylate, and n-butyl (meth)acrylate; nitrile group-containing monomers, such as (meth)acrylonitrile; alkylene glycol di(meth)acrylates, such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate; trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol di(meth)acrylate. Examples of the suitable silane coupling agents include polyol poly(meth)acrylates such as pentaerythritol di(meth)acrylate and pentaerythritol tetra(meth)acrylate, allyl compounds such as diallyl fumarate, diaryl itaconate and triallyl isocyanurate, and silane coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane and 3-acryloxypropyltriethoxysilane. One of the above-listed silane coupling agents may be used alone, or two or more of them may be used in combination. In this embodiment, the glass transition temperature of the other monomer as a homopolymer is preferably 70° C. or less. Furthermore, it is preferable that the swelling degree of the other monomer in an electrolyte solution is more than 1.40 times, or the swelling degree in an electrolyte solution cannot be measured due to dissolution in the electrolyte solution.
[0027] [Swelling degree of polymer particles after immersion in electrolyte] The degree of swelling of the polymer particles in an electrolyte solution is 1.30 times or less. By controlling the swelling ratio of the polymer particles in an electrolyte to 1.30 times or less, the swelling ratio of the polymer particles can be appropriately controlled, and excellent cycle characteristics can be obtained. From the above viewpoints, the degree of swelling of the polymer particles in an electrolyte is preferably 1.28 times or less, and more preferably 1.25 times or less. The degree of swelling of the polymer particles in an electrolyte solution is preferably 1.01 times or more. By making the degree of swelling of the polymer particles in an electrolyte 1.01 times or more, the polymer particles are given flexibility, and the ability to conform to the active material and the like can be improved, resulting in excellent cycle characteristics. From the above viewpoint, the degree of swelling of the polymer particles in an electrolyte solution is more preferably 1.05 times or more.
[0028] [Method for measuring swelling degree of polymer particles in electrolyte] The swelling degree of the polymer particles after immersion in an electrolyte solution is measured in the same manner as in the above-mentioned [Method for measuring swelling degree of a monomer in an electrolyte solution], except that a polymer polymerized only from a monomer is used as the polymer particles.
[0029] [Method of adjusting electrolyte swelling degree] The method of adjusting the electrolyte swelling degree of the polymer particles or various monomers in this embodiment to the above-mentioned numerical range is not particularly limited. For example, a method focusing on the solubility parameter (hereinafter also referred to as "SP value") of the monomer component can be mentioned. Specifically, a method of using a monomer component with a high SP value and a monomer component with a low SP value as a standard based on the SP value of a general electrolyte, a method of increasing or decreasing the content ratio of each monomer component while considering the SP value of each monomer component, and the like can be mentioned. In this specification, the SP value means the solubility parameter δ calculated by the following formula (A) using the cohesive energy density (E) and molar volume (V) of various atomic groups described in "RF Edors: Polym. Eng. Sci., 14[2], 147-154 (1974)". δ=ΣE / ΣV (A) (In formula (A), E and V respectively represent the E of various atomic groups and the molar volume V according to Fedors.)
[0030] The SP value of a typical electrolyte solution is, for example, about 11, but is not limited to the following. According to this example, a monomer component having an SP value of more than 11 can be treated as a high SP value component, and a monomer component having an SP value of less than 11 can be treated as a low SP value component.
[0031] [Glass transition temperature (Tg) of polymer particles] The polymer particles preferably have a glass transition temperature (Tg) of 20° C. or lower as measured by a differential scanning calorimeter (DSC). By ensuring that the Tg is 20° C. or lower, flexibility can be imparted to the polymer particles, improving their ability to conform to active materials and the like, resulting in excellent cycle characteristics. From the above viewpoints, Tg is more preferably 10° C. or lower, and further preferably 0° C. or lower. The polymer particles have a Tg of preferably −80° C. or higher, more preferably −60° C. or higher. When the Tg is within the above range, the adhesive strength of the polymer particles to the electrode at room temperature can be improved, and the cycle characteristics are well-balanced.
[0032] The polymer particles in this embodiment are measured with a differential scanning calorimeter (DSC) to obtain a DSC curve, and the DSC curve is differentiated to obtain a DDSC curve. The DDSC curve may have a plurality of peaks. In this case, the Tg obtained from the peak corresponding to the temperature range in which the slope of the DSC curve is maximum is the Tg in this specification.
[0033] [Method for measuring glass transition temperature of polymer particles] The composition containing the polymer particles is adjusted to pH 7.0 and dried to obtain a dried product. Using a differential scanning calorimeter (e.g., Hitachi High-Tech Science Corporation; DSC7020), the temperature is increased at a predetermined rate according to ASTM method (D3418-15), a differential scanning calorimeter curve of the polymer is obtained, and the glass transition temperature is determined.
[0034] The average particle size of the polymer particles is preferably 50 nm or more and 800 nm or less, more preferably 100 nm or more and 650 nm or less, and even more preferably 150 nm or more and 500 nm or less.
[0035] The average particle size of the polymer particles is measured using a particle size measuring device (e.g., FPAR-1000, manufactured by Otsuka Electronics Co., Ltd.) The measurement is performed using a concentrated probe under conditions of 25°C and a light intensity of 20,000 to 50,000, and the value of 50% of the cumulative particle size of the obtained scattering intensity distribution data is taken as the particle size.
[0036] (emulsifier) The composition of the present embodiment contains 0.01% by mass or more and 1.0% by mass or less of an emulsifier relative to 100% by mass of the polymer particles. The content of the emulsifier is smaller than that of the conventional composition, which tends to result in excellent defoaming properties in the composition of the present embodiment. When the content of the emulsifier is 0.01% by mass or more, the copolymerizability of the monomers is excellent. From the above viewpoints, the content of the emulsifier is preferably 0.1% by mass or more, and more preferably 0.2% by mass or more. When the content of the emulsifier is 1.0% by mass or less, the defoaming property is excellent. From the above viewpoints, the content of the emulsifier is preferably 0.9% by mass or less, and more preferably 0.7% by mass or less.
[0037] The emulsifier is not particularly limited, but examples thereof include anionic surfactants, nonionic surfactants, amphoteric surfactants, reactive surfactants, etc. The emulsifiers can be used alone or in combination of two or more kinds.
[0038] The anionic surfactant is not particularly limited, but examples thereof include sulfate esters of higher alcohols, alkylbenzene sulfonates, aliphatic sulfonates, and sulfate esters of polyethylene glycol alkyl ethers.
[0039] The nonionic surfactant is not particularly limited, but examples thereof include alkyl ester type, alkyl ether type, and alkyl phenyl ether type of polyethylene glycol.
[0040] The amphoteric surfactant is not particularly limited, but examples thereof include betaines such as lauryl betaine and stearyl betaine, and amino acid types such as lauryl-β-alanine, stearyl-β-alanine, and lauryl di(aminoethyl)glycine.
[0041] The reactive surfactant is not particularly limited, but examples thereof include polyoxyethylene alkylpropenylphenyl ether, α-[1-[(allyloxy)methyl]-2-(nonylphenoxy)ethyl]-ω-hydroxypolyoxyethylene, and the like.
[0042] Among the above, the emulsifier is preferably a sulfonic acid or a salt thereof. Specifically, examples of the emulsifier include sulfosuccinic acid compounds such as sodium dodecyldiphenyl ether sulfonate and dialkyl sulfosuccinate. As the emulsifier, commercially available products may be used, such as Newcol 707SF (manufactured by Nippon Nyukazai Co., Ltd.) and Pelex (registered trademark) SS-L (manufactured by Kao Corporation).
[0043] The composition of the present embodiment preferably further contains an isothiazolinone compound. The content of the isothiazolinone compound is preferably 0.0001% by mass or more and 1.0% by mass or less relative to 100% by mass of the polymer particles. When the content is within the above range, hysteretic viscosity behavior against shear force can be suppressed, and more stable coatability tends to be achieved.
[0044] The isothiazoline compound is not particularly limited, and various known compounds can be used. For example, 2-methyl-4-isothiazolin-3-one, 5-chloro-2-methyl-4-isothiazolin-3-one, 1,2-benzoisothiazolin-3-one, 2-n-octyl-4-isothiazolin-3-one, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, 2-ethyl-4-isothiazolin-3-one, 4,5-dichloro-2-cyclohexyl-4-isothiazolin-3-one, 5-chloro-2-ethyl-4-isothiazolin-3-one, 5-chloro-2-t-octyl-4-isothiazolin-3-one, 4-chloro-2-n-octyl-4-isothiazolin-3-one, Examples of the isothiocyanate include azolin-3-one, 5-chloro-2-n-octyl-4-isothiazolin-3-one, Nn-butyl-1,2-benzisothiazolin-3-one, N-butylbenzisothiazolin-3-one, N-methylbenzisothiazolin-3-one, N-ethylbenzisothiazolin-3-one, N-propylbenzisothiazolin-3-one, N-isobutylbenzisothiazolin-3-one, N-pentylbenzisothiazolin-3-one, N-isopentylbenzisothiazolin-3-one, N-hexylbenzisothiazolin-3-one, N-allylbenzisothiazolin-3-one, and N-(2-butenyl)benzisothiazolin-3-one. Among the above, 2-methyl-4-isothiazolin-3-one is preferred.
[0045] The composition of the present embodiment may optionally contain a defoamer. Examples of the defoaming agent include various defoaming agents based on mineral oil, silicone, acrylic, and polyether. When a defoaming agent is contained, the defoaming property tends to be more excellent. In this case, the types and blending ratios of the optional components are not particularly limited.
[0046] The composition of the present embodiment may contain a polymerization initiator as an optional component. The polymerization initiator is not particularly limited, but examples thereof include water-soluble polymerization initiators such as sodium persulfate, potassium persulfate, and ammonium persulfate, oil-soluble polymerization initiators such as benzoyl peroxide and lauryl peroxide, and redox-based polymerization initiators in combination with a reducing agent, etc. The polymerization initiators can be used alone or in combination of two or more kinds.
[0047] The composition of the present embodiment is a non-aqueous polymer composition for a secondary battery. Therefore, for example, the composition of the present embodiment preferably has a solid content of water-soluble components of 1.0 mass % or less. The solid content of the water-soluble component is measured by weighing 30 g of the composition of the present embodiment into a container and stirring it in a centrifuge at 50,000 rpm (revolutions per minute) for 2 hours. After separation, the composition is separated into an aqueous layer and a solid, and the aqueous layer is transferred to an aluminum dish and dried to calculate the solid content.
[0048] From the viewpoint of excellent defoaming properties and cycle characteristics, the nonaqueous secondary battery polymer composition of the present embodiment has a degree of neutralization when neutralized with a basic aqueous solution of preferably 5 mol % or more and less than 40 mol %, more preferably 10 mol % or more and less than 35 mol %, and even more preferably 15 mol % or more and less than 30 mol %.
[0049] (Application) The use of the composition of the present embodiment is not particularly limited. For example, the composition of the present embodiment can be used as a negative electrode material, a positive electrode material, a separator material, etc., and is preferably used as a positive electrode material. The composition of the present embodiment may contain various known optional components in addition to the polymer particles of the present embodiment, depending on the application.
[0050] <<Method for producing polymer composition for non-aqueous secondary battery>> The method for producing the composition of the present embodiment is not particularly limited, but it can be preferably produced by the following production method (hereinafter also referred to as the "production method of the present embodiment"). That is, in order to obtain a composition containing polymer particles, a method of carrying out emulsion polymerization using the above-mentioned raw material monomers, etc. is preferred. Appropriate seed particles can be used during polymerization, and the seed particles can also be obtained by normal emulsion polymerization. For the emulsion polymerization, a known method can be adopted, and the production can be carried out in an aqueous medium by appropriately using a polymerization initiator, a molecular weight regulator, a chelating agent, a pH regulator, an emulsifier, etc.
[0051] In the production method of this embodiment, the conditions such as stirring speed, polymerization temperature, reaction (polymerization) time, etc. are not particularly limited as long as the composition of this embodiment can be obtained. Typically, the stirring speed can be usually 50 rpm or more and 500 rpm or less, the polymerization temperature can be usually 50 ° C. or more and 100 ° C. or less, and the reaction time can be usually 3 hours or more and 72 hours or less.
[0052] In the method of the present embodiment, after the polymer particles are obtained as described above, the polymer particles are dispersed in a dispersion medium as necessary, and an optional component is added to obtain the composition of the present embodiment. As the dispersion medium, an organic solvent suitable for the active material can be used as necessary.
[0053] The composition of the present embodiment can be used in an electrode for a non-aqueous secondary battery, that is, the electrode for a non-aqueous secondary battery of the present embodiment may include the polymer composition for a non-aqueous secondary battery of the present embodiment. The electrode may be a positive electrode or a negative electrode, but is preferably a positive electrode.
[0054] (Positive electrode for non-aqueous secondary batteries) The positive electrode for a non-aqueous secondary battery of this embodiment contains the polymer composition for a non-aqueous secondary battery of this embodiment. Unlike the negative electrode, the positive electrode usually contains a conductive additive. The conductive additive is a very small particle (for example, nano-order) and has a very large specific surface area. Therefore, the conductive additive has a large contact area with other materials and a large number of contact points. In order to obtain sufficient adhesive strength at the above contact points, it is necessary to increase the amount of binder. In fact, the positive electrode usually contains about twice the amount of binder by mass compared to the negative electrode. When the amount of binder is increased, the amount of emulsifier is also increased in order to maintain the copolymerizability of the monomers. As a result, the foaming problem becomes more prominent in the positive electrode containing the conductive additive. On the other hand, this is relatively less of a problem in the negative electrode. The composition of the present embodiment exhibits excellent defoaming properties even when used in a positive electrode where the problem of foaming becomes more pronounced.
[0055] <Active material> The electrode of the present embodiment may contain an active material. The active material can include a positive electrode active material and a negative electrode active material.
[0056] The positive electrode active material is not particularly limited, but examples thereof include lithium-containing composite oxides, transition metal oxides, transition metal fluorides, and transition metal sulfides.
[0057] The lithium-containing composite oxide is not particularly limited, but examples thereof include lithium-containing composite metal oxides having a layered structure, lithium-containing composite metal oxides having a spinel structure, and lithium-containing composite metal oxides having an olivine structure. Examples of lithium-containing composite metal oxides having a layered structure include lithium-containing cobalt oxide (LiCoO2), lithium-containing nickel oxide (LiNiO2), lithium composite oxides of Co-Ni-Mn, lithium composite oxides of Ni-Mn-Al, and lithium composite oxides of Ni-Co-Al. Examples of lithium-containing composite metal oxides having a spinel structure include lithium manganate (LiMnO 4), or Li[Mn 3 / 2 M 1 / 2 ]O4 (wherein M is Cr, Fe, Co, Ni, Cu, etc.). Examples of lithium-containing composite metal oxides having an olivine structure include Li X Examples of the lithium phosphate-based compound include an olivine-type lithium phosphate-based compound represented by MPO4 (wherein M represents at least one selected from the group consisting of Mn, Fe, Co, Ni, Cu, Mg, Zn, V, Ca, Sr, Ba, Ti, Al, Si, B, and Mo, and X represents a number satisfying 0≦X≦2). Other examples include transition metal oxides, transition metal sulfides, and lithium-containing composite metal oxides of lithium and a transition metal. The transition metal fluoride is not particularly limited, but examples thereof include CuF2, NiF2, and the like. The transition metal sulfide is not particularly limited, but examples thereof include TiS2, TiS3, MoS3, and FeS2.
[0058] The negative electrode active material is not particularly limited, but examples thereof include materials capable of absorbing and releasing metal ions, specifically, carbon-based active materials, silicon-based active materials, and the like.
[0059] Examples of carbon-based active materials include graphite, carbon fiber, coke, hard carbon, mesocarbon microbeads (MCMB), baked furfuryl alcohol resin (PFA), and conductive polymers (poly-p-phenylene, etc.). Silicon-based active materials include silicon, SiO x (0.01≦x<2), alloys of silicon and transition metals, etc. Among the above, the active material preferably includes a negative electrode active material, more preferably includes a carbon-based active material, and further preferably includes graphite.
[0060] The nonaqueous secondary battery of the present embodiment includes the polymer composition for nonaqueous secondary batteries of the present embodiment. The nonaqueous secondary battery of the present embodiment may include the nonaqueous secondary battery electrode of the present embodiment.
[0061] The polymer composition for a non-aqueous secondary battery of the present embodiment can be used as a material for a positive electrode for a non-aqueous secondary battery. EXAMPLES
[0062] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to these examples. In the examples, the unit of content "parts" means "parts by mass" unless otherwise specified.
[0063] The details of the components in this example are as follows: (monomer) 2-EHA 2-Ethylhexyl acrylate EA Ethyl acrylate BA n-Butyl acrylate AA Acrylic Acid MAA Methacrylic acid AN Acrylonitrile AAm Acrylamide 3-Methacryloxypropyltrimethoxysilane 1,9-ND 1,9-nonanediol dimethacrylate The degree of swelling of each monomer in an electrolyte solution is shown in Tables 1 to 3. (emulsifier) Pelex SS-L (dodecyl diphenyl ether sulfonic acid sodium salt, manufactured by Kao Corporation, product name Pelex SS-L) NC707SF (Polyoxyethylene polycyclic phenyl ether sulfate ammonium salt, manufactured by Nippon Nyukazai Co., Ltd., Newcol 707-SF) Sodium dodecylbenzenesulfonate Sodium dodecylsulfonate Nonionic emulsifier (poly(oxyethylene) alkyl ether, Lion Specialty Chemicals Co., Ltd., Leocol TD-150)
[0064] [Example 1] A reactor was charged with 1.2 parts by mass of sodium dodecyl diphenyl ether sulfonate and 780 parts by mass of ion-exchanged water, and the temperature was raised to 70°C while stirring and maintained at that temperature. 3 parts by mass of sodium persulfate (hereinafter also referred to as "NPS") was added thereto. A monomer solution containing 525 parts by mass of 2-ethylhexyl acrylate, 72 parts by mass of methacrylic acid, and 3 parts by mass of 1,9-nonanediol dimethacrylate, 4 parts by mass of sodium dodecyl diphenyl ether sulfonate, and 600 parts by mass of ion-exchanged water were added thereto. The resulting mixture was mixed at 6,000 rpm for 5 minutes using a TK homomixer MARKII (manufactured by Tokushu Kika Kogyo Co., Ltd.). The mixture was combined to obtain a monomer emulsion. The obtained monomer emulsion was added dropwise, and the dropwise addition was completed in 2.5 hours while maintaining the temperature at 70°C, and polymerization was continued for 2 hours. The temperature was then raised from 70°C to 80°C and maintained for 1 hour to complete the polymerization, thereby obtaining polymer particles. Table 1 shows the blending amount of each monomer component and the content of the emulsifier relative to 100% by mass of all units derived from the ethylenically unsaturated monomers constituting the polymer particles. 0.0005% by mass of methylisothiazoline was added as an additive to 100% by mass of the obtained polymer particles. The polymerization rate was 99%. The polymerization rate was calculated by adding the solid content rate to the ratio of the amount of residue to the amount of all charged components. A composition having a neutralization degree shown in Table 1 was obtained by dropping a 10% by mass aqueous sodium hydroxide solution onto the obtained polymer particles. The neutralization degree was calculated from the charge ratio when polymerizing the polymer particles. Specifically, when the ethylenically unsaturated carboxylic acid or the alkali metal salt thereof used in the polymerization was taken as 100 mol%, the sodium hydroxide aqueous solution was dropped so that the molar ratio of the alkali metal salt of the ethylenically unsaturated carboxylic acid used in the polymerization and the alkali metal salt of the ethylenically unsaturated carboxylic acid produced by neutralization was the neutralization degree shown in Table 1. A secondary battery positive electrode was produced using the obtained composition as follows.
[0065] <Preparation of coating solution for secondary battery positive electrode> Carboxymethyl cellulose was added in a planetary mixer with a disperser in terms of solid content, and carbon black (Denka Black Li-400, manufactured by Denka Co., Ltd.) was added in an amount of 1.5 parts by mass as a conductive assistant, and the mixture was stirred and mixed for 10 minutes. Then, lithium iron phosphate (P600A, manufactured by Pulea Technology Industry Co., Ltd.) was added in an amount of 100 parts by mass as a positive electrode active material, and the mixture was stirred and mixed for 30 minutes. Ion-exchanged water was further added to adjust the total solid content to 50% by mass, and a coating liquid for a secondary battery positive electrode was prepared. The obtained coating liquid was used to evaluate the slurry foamability and slurry viscosity stability.
[0066] <Preparation of secondary battery positive electrode> The coating liquid was applied to one side of an aluminum foil having a thickness of 20 μm, which was to be a positive electrode current collector, using a die coater, and after drying at 130° C. for 3 minutes, it was compression molded using a roll press machine. At this time, the amount of the positive electrode active material applied was 250 g / m 2 , the bulk density of the active material is 3.00 g / cm 3 The surface roughness of the coating film was evaluated using the electrode obtained. The electrode thus obtained was used as a positive electrode for a secondary battery. The composition and the positive electrode for a secondary battery obtained as described above were used to evaluate various physical properties as described below. The results are shown in Table 1.
[0067] [Examples 2 to 14 and Comparative Examples 1 to 9] In each example, the compositions of Examples 2 to 14 and Comparative Examples 1 to 9 were prepared in the same manner as in Example 1, except that the type and / or amount of the monomer and emulsifier were changed so that the content of units derived from each monomer in the resulting polymer particles was as shown in Tables 1 to 3, and a coating solution for a secondary battery positive electrode was produced. The composition and the secondary battery positive electrode obtained as described above were used for various evaluations. The results are shown in Tables 1 to 3.
[0068] [Evaluation method] (Solid content of water-soluble components) First, 30 g of the composition of the Example or Comparative Example was weighed out and placed in a container, and stirred for 2 hours in a centrifuge at 50,000 rpm (revolutions per minute) (instrument name: Ultracentrifuge Optima L-90K, manufactured by Beckman Coulter, Inc.). After separation, the aqueous layer was separated from the solid matter, and the aqueous layer was transferred to an aluminum dish and dried to calculate the solid content.
[0069] (Monomer emulsion stability) The monomer emulsion was allowed to stand for a certain period of time, and the state of separation of the emulsion after standing was visually observed and evaluated. A: No separation occurred even after 2.5 hours from emulsification. B: Separation occurred more than 1 hour after emulsification and within 2.5 hours. C: Separation occurred more than 30 minutes after emulsification and within 1 hour. D: Separation occurred within 30 minutes after emulsification.
[0070] (Polymerization stability) After filtering the unneutralized composition using a 250 μm mesh, the residue remaining on the mesh was dried at 60° C. for one day. The resulting residue was weighed, and the amount of residue, which is the mass fraction, was calculated using the following formula. The smaller the amount of residue, the better the polymerization stability. Therefore, the polymerization stability was evaluated using the amount of residue. Residue amount [%] = (residue obtained) / (solid content of polymer particles) × 100 The amount of residue was then evaluated based on the following criteria. A: The amount of residue was less than 0.2%. B: The amount of residue was 0.2% or more and less than 0.5%. C: The amount of residue was 0.5% or more and less than 1.0%. D: The residue amount was 1.0% or more.
[0071] (Defoaming property) 100 g of the prepared coating liquid was added to a 200 mL cup, a ruler was fixed inside the cup, and the liquid level was measured. The coating liquid was stirred at 1000 rpm for 5 minutes using a Three-One Motor, placed in a vacuum container, and the pressure was reduced to 0.01 MPa for 5 minutes to raise the liquid level. The pressure was then returned to normal, the cup was removed, and the liquid level at reduced pressure was measured. The liquid level rise rate (%), which is the ratio of the liquid level at reduced pressure to the liquid level before stirring, was calculated, and the defoaming ability was evaluated according to the following criteria. Among the following evaluations, if the evaluation is A to C, the defoaming ability is excellent. A: The liquid level rise rate was 100% or more but less than 130%. B: The liquid level rise rate was 130% or more but less than 150%. C: The liquid level rise rate was 150% or more but less than 200%. D: The liquid level rise rate was 200% or more.
[0072] (Paint surface roughness) The obtained electrode was visually observed, and the number of bubbles present on the electrode surface in an area of 5 cm x 10 cm was counted. The number of bubbles obtained was evaluated according to the following criteria. A: There were no bubbles. B: The number of bubbles was 1 or more and less than 5. C: The number of bubbles was 5 or more and less than 10. D: The number of bubbles was 10 or more.
[0073] (Cycle characteristics) The secondary battery was manufactured by the following method using the negative electrode of the secondary battery. It was charged at a constant current of 1C between 4.2V and 3V at 45°C, and then discharged at a constant current of 1C to 3V. After repeating this 500 times, the rate of change in capacity at 1 / 3C before and after the cycle test was expressed as a percentage to evaluate the cycle characteristics. The higher this value, the better the cycle characteristics. Among the following evaluations, if the evaluation is A to C, the cycle characteristics are excellent. A: Capacity retention rate is 90% or more B: Capacity retention rate is 80% or more but less than 90% C: Capacity retention rate is 70% or more but less than 80% D: Capacity retention rate is less than 70%
[0074] (Glass transition temperature (Tg)) The composition containing the polymer particles was adjusted to pH 7.0 and dried at 130°C for 30 minutes to obtain a dried product. Using a differential scanning calorimeter (Hitachi High-Tech Science Corporation; DSC7020), the temperature was raised from -120°C to +230°C at a rate of 20°C / min according to ASTM method (D3418-15), a differential scanning calorimeter curve of the polymer particles was obtained, and the glass transition temperature was determined using the attached software. Whether the glass transition temperature was one or two or more was determined by finding the peaks judged by the software.
[0075] (Average particle size) The particle size of the particulate polymer was measured using an Otsuka Electronics FPAR-1000, which uses dynamic light scattering as its measurement principle. The measurement was performed using a concentrated probe at 25°C with a light intensity of 20,000 to 50,000, and the value of 50% of the cumulative particle size of the obtained scattering intensity distribution data was taken as the particle size.
[0076] (Electrolyte swelling degree) The composition containing the polymer particles was left to stand in an oven at 130°C for 1 hour to dry. The film of the polymer particles obtained by drying was cut out, and the mass of the film (Wa:g) was measured. The cut sample was placed in a 50mL vial together with 20g of a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 2 (volume ratio), and the mixed solvent was allowed to penetrate at 60°C for 1 day. Thereafter, the film was taken out, the electrolyte was wiped off, and the mass of the film (Wb:g) was measured. The film was washed with the above mixed solvent, the mass (Wb:g) was measured, and the swelling degree of the copolymer with respect to the electrolyte was calculated from the following formula. Electrolyte swelling rate (%) = (Wb / Wa) x 100
[0077] [Table 1]
[0078] [Table 2]
[0079] [Table 3]
[0080] As shown in Tables 1 to 3, the examples using the polymer composition for non-aqueous secondary batteries, which contains polymer particles having units U1 derived from ethylenic monomer M1 and units U2 derived from ethylenic monomer M2, the electrolyte swelling degree of the ethylenic monomer M1 is 1.40 times or less, the electrolyte swelling degree of the ethylenic monomer M2 is 1.20 times or less, the content of the units U1 is more than 50 mass% and the content of the units U2 is 5 mass% or more and less than 50 mass%, the electrolyte swelling degree of the polymer particles is 1.30 times or less, and the emulsifier is 0.01 mass% or more and 1.0 mass% or less with respect to 100 mass% of the polymer particles, were excellent in the evaluation of defoaming property and cycle characteristics. On the other hand, Comparative Examples 1 and 3 in which the content of units U1 was not more than 50 mass% were inferior in cycle characteristics. Comparative Example 2 in which the content of units U2 was not 5 mass% or more and not less than 50 mass% was inferior in cycle characteristics. Comparative Examples 4 and 6 to 9 in which the content of emulsifier was not 1.0 mass% or less were inferior in defoaming ability and cycle characteristics. Comparative Example 5 in which the swelling degree of the polymer particles in the electrolyte was not 1.30 times or less was inferior in cycle characteristics.
Claims
1. The polymer particles have a unit U1 derived from an ethylenic monomer M1 and a unit U2 derived from an ethylenic monomer M2, The ethylenic monomer M1 has an electrolyte swelling degree of 1.40 times or less; The ethylenic monomer M2 has an electrolyte swelling degree of 1.20 times or less; the content of the unit U1 is more than 50% by mass, and the content of the unit U2 is 5% by mass or more and less than 50% by mass, based on 100% by mass of all units derived from ethylenically unsaturated monomers constituting the polymer particles; The degree of swelling of the polymer particles in an electrolyte solution is 1.30 times or less, The non-aqueous secondary battery polymer composition comprises an emulsifier in an amount of 0.01% by mass or more and 1.0% by mass or less relative to 100% by mass of the polymer particles.
2. The polymer composition for a non-aqueous secondary battery according to claim 1, wherein the emulsifier is a sulfonic acid or a salt thereof.
3. 2. The polymer composition for a non-aqueous secondary battery according to claim 1, wherein the degree of neutralization when neutralized with a basic aqueous solution is 5 mol % or more and less than 40 mol %.
4. 2. The polymer composition for non-aqueous secondary batteries according to claim 1, wherein the solid content of the water-soluble component is 1.0 mass % or less.
5. 2. The polymer composition for a non-aqueous secondary battery according to claim 1, wherein the content of the unit U1 is more than 50 mass% and the content of the unit U2 is 5 mass% or more and less than 25 mass% with respect to 100 mass% of all units derived from the ethylenically unsaturated monomer constituting the polymer particle.
6. 2. The polymer composition for a non-aqueous secondary battery according to claim 1, wherein the ethylenic monomer M1 comprises 2-ethylhexyl acrylate.
7. 2. The polymer composition for a non-aqueous secondary battery according to claim 1, wherein the ethylenic monomer M2 comprises an ethylenically unsaturated carboxylic acid or an alkali metal salt thereof.
8. 2. The polymer composition for non-aqueous secondary batteries according to claim 1, wherein the ethylenic monomer M2 comprises (meth)acrylic acid or an alkali metal salt thereof.
9. 2. The polymer composition for a non-aqueous secondary battery according to claim 1, wherein the polymer particles have a glass transition temperature of 20[deg.] C. or lower as measured by a differential scanning calorimeter (DSC).
10. 2. The polymer composition for a non-aqueous secondary battery according to claim 1, wherein the average particle size of the polymer particles is 50 nm or more and 800 nm or less.
11. Further containing an isothiazolinone compound, 2 . The polymer composition for a non-aqueous secondary battery according to claim 1 , wherein the content of the isothiazoline compound is 0.0001% by mass or more and 1.0% by mass or less with respect to 100% by mass of the polymer particles.
12. A positive electrode for a non-aqueous secondary battery comprising the polymer composition for a non-aqueous secondary battery according to any one of claims 1 to 11.
13. A non-aqueous secondary battery comprising the polymer composition for non-aqueous secondary batteries according to any one of claims 1 to 11.
14. 12. Use of the polymer composition for a non-aqueous secondary battery according to claim 1 as a material for a positive electrode of a non-aqueous secondary battery.
Citation Information
Patent Citations
Non-aqueous secondary battery polymer composition and non-aqueous secondary battery
WO2022131253A1